Inculcation of Entrepreneurship among Rural Pepper Farmers in Sarawak - Khalid, Abdul Rahim; Anita, Rosli; Audrey, Liwan (UPM, 2012)
Pepper farming in Sarawak has both economic and political significance in the state. While some entrepreneurs are very education and motivation.